A Study of Pattern, Magnitude and Trend in the Growth of Expenditure of Tirumala Tirupati Devasthanams, Andhra Pradesh - M. Kumudini AND Dr. B. Bhagavan Reddy (Commerce Spectrum, 2014)
Temple worship is an age old culture in India. Temples in general have been following a pragmatic and a philanthropic policy in their monetary transactions. They stimulate and encourage local trade and industry. The construction, maintenance, daily routine services and administration of temples have offered employment to many. They have started giving importance to economic and social upliftment of the society. They serve as financial institutions; consumers; employers; landlords; centers of learning; economic entity and so on. Among the Hindu religious institutions, the Tirumala Tirupati Devasthanams (TTD) is the biggest religious institution in the country. Its expenditure is being utilised for the maintenance of temples, besides service departments for temples and pilgrims. The TTD is running several educational institutions and also maintains a cultural centre to preserve ancient Indian culture. For the propagation of Hindu religion, several projects have also been organised. There is a full-fledged engineering division, which undertakes construction of cottages, choultries, kalyanamandapams, supply of electricity, water works etc. The present study mainly deals with the objectives, pattern and trend in the progress of expenditure of the TTD. An attempt is made here to analyse the expenditure at the aggregate level; in terms of revenue and capital; temple and non-temple; religious and non-religious; pilgrim related and non-pilgrim related; various heads; departments and surplus/deficit